2008
DOI: 10.1007/s11259-008-9194-z
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of Miconazole and Polymyxin B on microbial pathogens

Abstract: The therapeutic value of antibiotics depends on the susceptibility of the infecting microorganism and the pharmacological profile of the drugs. To assess the value of an antibiotic combination of polymyxin B and miconazole this study examined the in vitro synergistic potential of the two drugs on Gram-negative and Gram-positive bacteria and yeast. Antifungal and antibacterial activity was tested by minimum inhibitory concentration (MIC) of broth macrodilution and urea broth microdilution, by fluorescence micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 34 publications
9
41
0
Order By: Relevance
“…Regarding fungi, synergy of PMX and MCZ has also been demonstrated against Candida albicans [24] and M. pachydermatis. However, with reference to M. pachydermatis, data has only been collected for one strain, which was, furthermore, a reference strain coming from a fungal collection (M. pachydermatis CBS 1879) [12]. Our data confirm that a synergistic interaction of PMX and MCZ exists against field strains of M. pachydermatis.…”
supporting
confidence: 59%
See 4 more Smart Citations
“…Regarding fungi, synergy of PMX and MCZ has also been demonstrated against Candida albicans [24] and M. pachydermatis. However, with reference to M. pachydermatis, data has only been collected for one strain, which was, furthermore, a reference strain coming from a fungal collection (M. pachydermatis CBS 1879) [12]. Our data confirm that a synergistic interaction of PMX and MCZ exists against field strains of M. pachydermatis.…”
supporting
confidence: 59%
“…Up until now, synergy between PMX and MCZ has been demonstrated against different bacterial species often involved in canine otitis externa, such as Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli [11,12], but in most cases experiments have been conducted on reference strains. Moreover, Pietschmann et al (2013) have recently shown an in vitro synergy of PMX and MCZ against field strains (i.e.…”
Section: Synergy Of Of Miconazole and Polymyxin B Against Malassezia mentioning
confidence: 99%
See 3 more Smart Citations